Statistical analysis, source apportionment, and toxicity of particulate- and gaseous-phase PAHs in the urban atmosphere - Singh, Bhupendra Pratap; Zughaibi, Torki A.; Alharthy, Saif A.; Al-Asmari, Ahmed I.; Rahman, Shakilur (Frontiers in Public Health, 2023)
The concentrations of particulate and gaseous Polycyclic Hydrocarbons Carbon (PAHs) were determined in the urban atmosphere in different seasons (winter, summer, and monsoon). The samples were collected by using air metric (particulate phase) and charcoal tube (gaseous phase) and analyzed through Gas chromatography. The principal component and correlation were used to identify the sources of particulate and gaseous PAHs during different seasons. The mean concentration of the sum of total PAHs (TPAHs) for particulate and gaseous phases. PAHs at all the sites were found to be higher in the winter season (165.14 ± 50.44 ng/m3 and 65.73 ± 16.84 ng/m3) than in the summer season (134.08 ± 35.0 ng/m3 and 43.43 ± 9.59 ng/m3), whereas in the monsoon season the concentration was least (68.15 ± 18.25 ng/m3 and 37.63 ± 13.62 ng/m3). Seasonal variations of PAHs accounted for over 86.9%, 84.5%, and 94.5% for the summer, monsoon, and winter seasons, respectively. The strong and positive correlation coefficients were observed between B(ghi)P and DahA (0.922), B(a)P and IcdP (0.857), and B(a)P and DahA (0.821). In addition to this, the correlation between Nap and Flu, Flu and Flt, B(a)P, and IcdP showed moderate to high correlation ranging from 0.68 to 0.75 for the particulate phase PAHs. The carcinogenic health risk values for children and adults at all sites were calculated 4.53 x 10-6, 1.22 x 10-5 for gaseous phase PAHs and 2.36 x 10-5, 6.35 x 10-5 particulate phases PAHs, respectively. The carcinogenic health risk for current results was found to be relatively higher than the prescribed standard of the Central Pollution Control Board (1.0 x 10-6).